2016
DOI: 10.1097/iae.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Optical Coherence Tomographic Hyperreflective Foci and Visual Outcomes After Anti-Vegf Treatment in Neovascular Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy

Abstract: The number of HF at subretinal layer on spectral domain optical coherence tomography at baseline might predict the final visual acuity after treatment in nAMD and PCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…Kang et al found that the number of HRF at baseline was inversely associated with final VA in patients with diabetic macular edema treated with intravitreal bevacizumab [ 23 ]. The same group reported similar findings in patients with branch retinal vein occlusion [ 8 ], neovascular age-related macular degeneration and polypoidal choroidal neovascular vasculopathy [ 24 ].…”
Section: Discussionmentioning
confidence: 64%
“…Kang et al found that the number of HRF at baseline was inversely associated with final VA in patients with diabetic macular edema treated with intravitreal bevacizumab [ 23 ]. The same group reported similar findings in patients with branch retinal vein occlusion [ 8 ], neovascular age-related macular degeneration and polypoidal choroidal neovascular vasculopathy [ 24 ].…”
Section: Discussionmentioning
confidence: 64%
“…The power of previous investigations has, however, been limited by the laborious quantification and poor reproducibility of the changes identified in the outer retinal bands. 35 Nevertheless, in an observation that lasted a minimum of 12 months after initiation of anti-VEGF therapy, the initial preservation of a foveal ELM was shown to be correlated with better final VA. 52 A retrospective study with a mean follow-up of 6 months showed that the length of disruption of the EZ at baseline correlated positively with the final VA. 53 Further, a posthoc analysis of CATT found the EZ was absent in the foveal center more often in eyes with underlying foveal SHRM. 49 However, analysis of the ELM alone did not reveal similar results.…”
Section: Risk Of Progressionmentioning
confidence: 98%
“…This feature of exudative disease also shows statistically significant reduction during anti-VEGF therapy. [51][52][53][54]…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Studies have also suggested increased number of hyper reflective foci on SD-OCT as a predictive factor for poorer visual outcomes following treatment for PCV. [ 35 ] These hyper reflective spots are non-specific biomarkers caused by migration of intraretinal microglial cells representing on-going inflammation and are also seen in patients with other retinal vascular diseases including diabetic macular edema and retinal vein occlusion. [ 36 ]…”
Section: Diagnosis Of Pcvmentioning
confidence: 99%